Integrating Plan for Backwaters Transportation with Tourism Development: A Case Study of Kochi City Region - V. B. Bigith AND H. S. Kumara (International Journal of Research in Engineering, Science and Management, 2019)
Kerala is one of the fastest growing urbanising states in India and half of the population residing in urban areas. The Kochi city region is having a population of 2.119 million (Census, 2011) and it is situated on the western coast of India in Ernakulam district of Kerala. Kochi is abundantly blessed with waterways with over 1,100 kms. However, only forty kilometers out of these are considered navigable for motor boats (IWAI). The aim of study is to evaluate whether and how Inland Water Transport can provide a valuable input to reimagining Kochi City Region through tourism development. The objective of the study is to assess existing Inland water transportation with tourism development and integrating plan for Backwaters Transportation with Tourism Development. This paper identifies a conceptual framework within which the effect of Backwater transportation with tourism development. The study is mainly based on secondary sources of data including availability of infrastructure facilities at ferry station and tourist spots etc. Visual survey was conducted in ferry stations, tourist spots and tourist circuits and about 70 structured interview questionnaires were used to elicit the information from tourist, private boat operators and stakeholders in Kochi City Region through Opinion Survey. This paper attempts to analyze the efficiency of Backwaters transport with tourism development and explore sustainable development of tourism through integrating inland water transport for reimagining the Kochi City Region.